(3GdcGed aj GdJGQjNs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ,J (B630 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje ef Chd GdhLhO CeG HYO aEfi de CRd HGdeWGdYI cJH GdJhGQjN heYQaI eG ajgG eDKQkG ddEWdGY s
(3BNQgG (B:s
(3GLJeY ef HGdHUQI ef GdMQK Hf YHO GdeWdH Hf eMeO Hf LYaQ ahdhg CeQge hGfbVJ GdOhdI GdCehjI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1380s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs